THE ROLE OF PARENTAL SUPPORT AND SELF-EFFICACY IN STUDENTS CAREER DECISION-MAKING IN VOCATIONAL EDUCATION - Salma, Maulida Asyifa; Nurmalasari, Dewi; Sumiati, Ati (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2025)
The purpose of this study was to determine how self-confidence and parental support influence students' career decision-making in vocational high schools. Using a quantitative approach and a purposeful random sampling procedure, 118 students were selected as a sample from the 179 students who answered, as indicated by the Isaac and Michael table. Questionnaires were used to gather data, and SPSS version 21 was used for analysis.  The analysis method includes prerequisite tests, conventional assumption tests, and hypothesis testing, including t-tests, f-tests, and the coefficient of determination. The study's findings suggest that students' vocational decision-making is positively and significantly impacted, partially and simultaneously, by both parental support and self-efficacy. These results highlight how crucial student self-belief and parental participation are in fostering their preparedness for the profession.  In practice, the findings of this study can be used as a foundation or point of reference for more research.